Creating a Community-Based Intervention to Increase Health Insurance Coverage in the A-Duiem Administrative Unit, Sudan, 2018–2019: A Step Towards Universal Health Coverage - Samia Y. I. Habbani; Egbal A. B. A. Karaig; Sumaia M. Al-Fadil; Maisa El-Fadul; Siddik M. A. Shaheen; Nahid A. A. Gadir; Hashim Al-Amin S. Abu Zaid; Elfatih M. Malik (Public Health, 2025)
Background: Community engagement has proved effective in increasing access to healthcare including health insurance, in developed and developing countries. Aim: The study aims at designing and testing the effectiveness of engaging the community in awareness-raising and increment of health insurance coverage. Methods: The study was a social interventional community-based study, conducted in A-Duiem Administrative Unit, A-Duiem Locality, Sudan. Baseline data on enrollment in health insurance was collected from 800 heads of households, whereas data on knowledge and attitudes about health insurance was collected from 420 heads of non-insured households using a standardized questionnaire. Strategies to scaleup health insurance through community engagement was collected from community leaders, local authorities, and health insurance policymakers through in-depth interviews and focus group discussions. The community promotion package of health insurance was implemented for one year and post-intervention data were collected from 420 heads of households. Quantitative data were analyzed using SPSS version 20. Statistical significance was set at p<0.05 when the confidence interval was 95%. Qualitative data was analyzed manually using the thematic approach. Results: The study showed significant improvement in the knowledge of the heads of the non-insured households about health insurance after the intervention; knowledge about the enrollment process and service’s package has increased from 34.4% to 61.8% and from 55.8% to 84.7% respectively (p-value 0.0001 in both). The health insurance coverage increased by 17.3% with a significant difference and p-value at 0.0001. Conclusion: The study concluded that community members have a considerable role in awareness-raising and scaling up of health insurance coverage if they are properly organized, trained, monitored, and supervised. The insufficient commitment of local officials in the unit was a challenge to address during further testing and expansion of the experience.